Penyuluhan Literasi Bagi Ibu-Ibu PKK Guna Mengurangi Ketergantungan Anak Pada Produk Gawai. - Tulasmi Tulasmi; Titania Mukti; Ryan Yuniawan; Vira Prajna Cantika (BUDIMAS : JURNAL PENGABDIAN MASYARAKAT, 2021)
Literacy is a process that starts from reading interest, then reading habit, reading ability. The existence of gadget products that were originally used to help human activities turned out to have a negative impact. Nowadays, children's dependence on gadget products has become a social problem that often occurs. This can be seen in the initial survey before the literacy counseling was held in Jenengan Hamlet, Tempel, Sleman, DIY. The habit of children interacting with digital technology such as smart phones begins to lead to negative dependence. This service program is designed using lecture and discussion methods about the importance of literacy and prevention of children's dependence on gadget products. After attending the counseling, it was found that the Wilcoxon test results on the participants' pre-test and post-test scores showed an asymp.sig value of 0.000 which means that there is a significant difference between the literacy of the PKK women in Jenengan village before the training and after the training. with a positive mean value of pre-test and post-test is 19 which indicates that the training that has been implemented has succeeded in increasing the majority of the trainees.